Baseline inflammatory status affects the prognostic impact of statins in patients with peripheral arterial disease - Kentaro Jujo; Daisuke Ueshima; Takuro Abe; Kensuke Shimazaki; Yo Fujimoto; Tomofumi Tanaka; Teppei Murata; Toru Miyazaki; Michiaki Matsumoto; Hideo Tokuyama; Tsukasa Shimura; Ryuichi Funada; et al. (American Heart Journal Plus)
Background: Statins bring favourable effects on the clinical prognosis of patients with atherosclerotic disease partly through their anti-inflammatory properties. However, this effect has not been fully verified in patients with peripheral arterial disease (PAD). We aimed to test whether statins exert different prognostic effects depending on the degrees of inflammation in patients with PAD. Methods: This study was a sub-analysis of a multicenter prospective cohort of 2321 consecutive patients with PAD who received endovascular therapy (EVT). After excluding patients without information on C-reactive protein (CRP) levels at the time of index EVT, 1974 patients (1021 statin users and 953 non-users) were classified into four groups depending on CRP levels: low CRP (<0.1 mg/dL), intermediate-low CRP (0.1–0.3 mg/dL), intermediate-high CRP (0.3–1.0 mg/dL), and high CRP (>1.0 mg/dL). A composite of death, stroke, myocardial infarction, and major amputation as the primary endpoint was compared between statin users and non-users in each CRP category. Results: During the median observation period of 316 days, the primary composite endpoint occurred in 112 (11.0 %) statin users and 178 (18.7 %) non-users (log-rank test, p < 0.001). However, statin therapy was associated with significantly lower event rates only in the intermediate-high- and high-CRP categories (p = 0.02 and p = 0.008, respectively). Multivariable Cox regression analysis revealed that statin use was independently associated with the primary endpoint only in the high-CRP category (adjusted hazard ratio: 0.64 [95 % confidence interval: 0.41–0.98]). Conclusion: Statins may exert favourable prognostic effects in patients with PAD and highly elevated CRP levels.